Persistent Wnt/β-catenin signaling in mouse epithelium induces the ectopic Dspp expression in cheek mesenchyme. (2nd January 2019) - Zhou, Nan; Li, Nan; Liu, Jing; Wang, Yu; Gao, Jun; Wu, Yingzhang; Chen, Xiaoyan; Liu, Chao; Xiao, Jing
ABSTRACT: Tooth development is accomplished by a series of epithelial-mesenchyme interactions. Epithelial Wnt/β-catenin signaling is sufficient to initiate tooth development by activating Shh, Bmps, Fgfs and Wnts in dental epithelium, which in turn, triggered the expression of odontogenic genes in the underlying mesenchyme. Although constitutive activation of Wnt/β-catenin signaling in oral ectoderm resulted in the continuous tooth formation throughout the life span, if the epithelial Wnt/β-catenin signaling could induce the mesenchyme other than oral mesenchyme still required to be elucidated. In this study, we found that in the K14-cre; Ctnnb1 ex3f mice, the markers of dental epithelium, such as Pitx2, Shh, Bmp2, Fgf4, and Fgf8, were not only activated in the oral ectoderm, but also in the cheek epithelium. Surprisingly, the underlying cheek mesenchymal cells were elongated and expressed Dspp . Further investigations detected that the expression of Msx1 and Runx2 extended from oral to cheek mesenchyme. These findings suggested that epithelial Wnt/β-catenin signaling was capable of inducing Dspp expression in non-dental mesenchyme. Moreover, Dspp expression in the K14-cre; Ctnnb1 ex3f oral mesenchyme was activated earlier than that in the wild type littermates. In contrast, although the elongated oral epithelial cells were detected in the K14-cre; Ctnnb1 ex3f mice, the Amelogenin expression was suppressed. The differential effects of the persistent epithelial Wnt/β-catenin signaling on ameloblast and odontoblast differentiation might result from the altered BMP signaling. In summary, our findings suggested that the epithelial Wnt/β-catenin signaling could induce craniofacial mesenchyme into odontogenic program and promote odontoblast differentiation.